Assessment of the impact of a “user generated” video in the communication of marine environmental threats - Jorge, Miguel; Pinto, Bruno; Boaventura, Diana (Frontiers in Communication, 2024)
This study aimed to assess the impact of a "user generated" video in communicating about marine environmental threats, specifically to one hundred and fifty-one young adults enrolled in two different schools: a private higher education school, and a public university, both in the Lisbon metropolitan area (Portugal). The video's impacts in the cognitive and emotional fields were assessed by comparing them to the impacts of an outreach text similar in content and duration of exposure. A pretest/post-test methodology was used to evaluate short-term impacts, and a follow-up test was applied to gauge medium-term impacts. Additionally, short focus group sessions further explored topics such as media consumption preferences and trends. The results suggest that "user generated" video has a similar impact to an outreach text in the cognitive field, and a bigger impact in the emotional field when it comes to promoting positive emotions and feelings. Therefore, when used to its full potential, this type of media can be a suitable way to communicate about science and environmental topics, particularly marine environmental threats, and a valuable tool to raise public awareness.